Pola asuh permisif dan insecure attachment sebagai pemicu kenakalan remaja? - Saputra, Egy Oktadrian; Saragih, Sahat; Rini, Amanda Pasca (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract The puberty period is one of the important development periods in the life of every human being. It is during this period that teenagers compete to start looking for their identity. Juvenile delinquency is not only a social problem, but also a developmental problem. In this research, the population used was 120 grade 10 students at SMA Dharma Wanita Surabaya. The sampling technique used was saturated sampling. When data was collected, only 110 people could fill out the questionnaire. This research is included in the quantitative research method with a correlational type. The juvenile delinquency scale used in this research was prepared based on aspects proposed by Sarwono (2002). The permissive parenting style scale is based on aspects proposed by Hurlock (1993). The insecure attachment scale is based on aspects proposed by Armsden & MarkT. Greenberg (1987) The results of this study show that there is an insignificant positive relationship between permissive parenting and insecure attachment and juvenile delinquency. Suggestions that researchers can give to research participants are that students are expected to have the courage to convey to their parents if they feel that their parents are implementing all aspects of permissive parenting. It is hoped that parents will further increase their attachment to their children. Future researchers are expected to use Bartholomew & Horowitz's theory (1991) to deepen the aspects and tools for measuring insecure attachment. Abstrak Periode Baligh adalah satu diantara periode perkembangan penting dalam kehidupan setiap umat manusia. Pada masa inilah para remaja berlomba-lomba untuk mulai mencari jati diri.Kenakalan remaja bukan hanya menjadi masalah sosial, tetapi juga masalah perkembangan. Pada penelitian ini, populasi yang digunakan yaitu siswa kelas 10 SMA Dharma Wanita Surabaya yang berjumlah 120 orang. Teknik sampling yang digunakan yakni sampling jenuh ada saat pengambilan data hanya 110 orang yang dapat mengisi kuesioner. Penelitian ini termasuk ke dalam metode penelitian kuantitatif dengan jenis korelasional. Skala kenakalan remaja yang digunakan dalam penelitian ini disusun berdasarkan aspek yang telah dikemukakan oleh Sarwono (2002). Skala pola asuh permisif disusun berdasarkan aspek yang dikemukakan oleh Hurlock (1993) Skala insecure attachment disusun berdasarkan aspek yang dikemukakan oleh Armsden & MarkT. Greenberg (1987) Hasil dalam penelitian ini menunjukkan bahwasannya terdapat hubungan positif yang tidak signifikan antara pola asuh permisif dan insecure attachment dengan kenakalan remajaSaran yang bisa diberikan peneliti kepada partisipan penelitian adalah Siswa diharapkan berani menyampaikan kepada orangtua apabila dirasa orangtuanya menerapkan seluruh aspek pola asuh permisif. Bagi orang tua diharapkan agar lebih meningkatkan lagi kelekatannya kepada anak Bagi peneliti selanjutnya adalah diharapkan menggunakan teori miliki Bartholomew & Horowitz (1991) guna memperdalam aspek serta alat ukur insecure attachment.